2008
DOI: 10.1016/j.atherosclerosis.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

ALOX5AP variants are associated with in-stent restenosis after percutaneous coronary intervention

Abstract: Background-Use of drug-eluting stents (DES) has reduced in-stent restenosis after percutaneous coronary intervention (PCI); however, DES are associated with late stent thrombosis. There is no accurate way to predict in-stent restenosis, although risk factors for atherosclerosis overlap those for in-stent restenosis. Therefore, we evaluated atherosclerosis candidate genes for association with in-stent restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Consistent with this notion, variations in genes of the LT biosynthetic pathway have been associated with increased CVD risk (14)(15)(16)(17)(18), although some studies have reported equivocal results or no association (19)(20)(21). The promoter region of the ALOX5 gene has between three and eight tandem repeats of a consensus binding site for the transcription factors Sp1 and Egr1, with the most frequent allele having fi ve such repeats ( 22 ).…”
Section: Ethical Review and Trial Registrationmentioning
confidence: 53%
“…Consistent with this notion, variations in genes of the LT biosynthetic pathway have been associated with increased CVD risk (14)(15)(16)(17)(18), although some studies have reported equivocal results or no association (19)(20)(21). The promoter region of the ALOX5 gene has between three and eight tandem repeats of a consensus binding site for the transcription factors Sp1 and Egr1, with the most frequent allele having fi ve such repeats ( 22 ).…”
Section: Ethical Review and Trial Registrationmentioning
confidence: 53%
“…3 Furthermore, the polymorphisms within the gene encoding the 5-LO activating protein (FLAP), which have been associated with an increased risk of myocardial infarction and stroke, 4 were recently reproduced in restenosis patients. 5 In the latter study, 2 of the FLAP gene polymorphisms studied were independent prognostic factors in predicting in-stent restenosis 6 months after PCI. 5…”
mentioning
confidence: 99%
“…3 Furthermore, the polymorphisms within the gene encoding the 5-LO activating protein (FLAP), which have been associated with an increased risk of myocardial infarction and stroke, 4 were recently reproduced in restenosis patients. 5 In the latter study, 2 of the FLAP gene polymorphisms studied were independent prognostic factors in predicting in-stent restenosis 6 months after PCI. 5 Although no previous study has evaluated the effects of antileukotrienes on in-stent restenosis, the available data have provided indications for potential effects of LTs in the response to vascular injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leukotrienes are arachidonic acid derivatives long known for their inflammatory properties and their involvement with a number of complex human diseases, most particularly asthma. Several genetic linkage and associations studies as well as gene expression studies have shown an association of the leukotriene biosynthesis pathway to CAD (Dwyer et al, 2004, Helgadottir et al, 2004, 2005b,a, Lohmussaar et al, 2005, Shah et al, 2008. Helgadottir et al (2004) identified a four-SNP haplotype (HapA) spanning the ALOX5AP gene that conferred a nearly two times greater risk of MI and stroke in a case-control cohort.…”
Section: Introductionmentioning
confidence: 99%